The Effect of Nanocurcumin Particle Sizes on the Inhibitory Potential on Staphylococcus aureus and Escherichia coli - Tnunay, Fiona Rosslyn; Ricky, Donn Richard; Tobing, Joshua H. L. (Jurnal Biologi Tropis, 2025)
Increasing antibiotic resistance against major pathogens like Staphylococcus aureus and Escherichia coli are necessitates as alternative antimicrobials. Curcumin, known for its antibacterial properties, suffers from low bioavailability; thus, developing it into nanocurcumin using the stabilizer PVP is aims in enhancing its efficacy. This study was conducted to investigate the effect of nanocurcumin particle sizes (controlled by three PVP K30 concentrations: 1.5, 3.0, and 4.5 g/mL) on its inhibitory potential on Staphylococcus aureus and Escherichia coli. The research is a true laboratory experimental design, synthesizing nanocurcumin via a Rotor Stator Homogenizer and assessing antibacterial activity using the disc diffusion method on Mueller Hinton Agar (MHA), with inhibition zone diameters are analyze using One-Way ANOVA. All tested samples exhibit weak inhibitory potential. The ANOVA revealed no significant effect against Staphylococcus aureus (p = 0.377), but shows a significant effect against Escherichia coli (p = 0.042). These finding shows that particle size variations of nanocurcumin influence against Gram-negative bacteria, with the smallest average particle size (20.6 nm) obtained at 1.5 g/mL PVP K30. In conclusion, nanocurcumin size variations significantly affect the inhibition against Escherichia coli but not against Staphylococcus aureus, a differential effect attributed to the distinct cell wall structures of the two bacteria types. Future studies are recommended to explore optimization methods to improve nanocurcumin's efficacy, especially against Staphylococcus aureus.